Literasi informasi di perpustakaan - Abdul Karim Batubara (UIN Sumatera Utara, 2015)
Information literacy is an important skill for librarian todays in global era, so that information literacy for librarian not only marked literate and able to read it only. However, the actual application is more than that, because it was supposed mastery of information literacy becomes an integral part of the librarian. Librarians should be manager of science, because every day struggling with a variety of resources. In response to this, then inevitably the librarian should be able to search the information in the library either manually or online.